An automated radiosynthesis of [18F]DPA-714 on a commercially available radiosynthesizer, Elixys Flex/Chem. (February 2022) - McCauley, Katelyenn S.; Wilde, Justin H.; Bufalino, Sophia M.; Neumann, Kiel D.
Abstract: [ 18 F]DPA-714 is a radiotracer specific to the translocator protein (TSPO) and is useful for in vivo Positron Emission Tomography imaging studies. In this report, we have developed an automated radiosynthesis of [ 18 F]DPA-714 on a commercially-available radiosynthesis platform, which comports with USP <823> guidelines. The wide availability of the radiosynthesis module and ease of dissemination of the production sequence will facilitate preclinical and clinical research of TSPO-related pathology. Highlights: A USP <823> compliant [ 18 F]DPA-714 radiosynthesis is now available Synthesis of a radiochemical precursor is optimized Low yields of a radiochemical precursor were the result of an elimination product formed in situ